A Comparative Study to Evaluate The Effectiveness of Warm Sitz Bath Versus Infra-Red Light on Episiotomy Wound Healing Among Postnatal Mothers in Selected Hospital - JamunaR, JamunaR; Deshpande, Jyotsna; Shiroor, Geeta (Journal of Neonatal Surgery, 2025)
Postpartum complications like haemorrhage, hypertension, pulmonary embolism, and sepsis can cause physical discomfort and psychological distress for mothers. Common surgical complications include wound breakdown, breast abscess, and urinary fetal incontinence. Early identification and proper intervention can help mothers recover and restore their pre-pregnancy state. Episiotomy, a common obstetric operation, is believed to reduce fetal trauma and protect maternal soft tissues. Aim of thestudy: The main aim of the study was to evaluate the effectiveness of warm sitz bath versus infra red light on episiotomy wound healing among postnatal mothers in selected hospital Methodology:A comparative study was conducted among mothers who gave birth to the baby with normal delivery and had episiotomy in selected hospital, Quasi experimental- pretest post-test with control group research design was used in this study. The data was collected through interview schedule from the subjects regarding their demographic and obstetrical variables, Universal pain assessment scale and REEDA scale were used to assess the level of episiotomy pain and wound healing among the postnatal mothers. Result:The study analysed pain levels in experimental groups 1 and 2, with 67% experiencing severe pain and 33% having moderate pain. After the intervention, 50% reported moderate to severe pain, while 60% experienced severe pain. Pre-intervention pain scores varied, with 53% reporting moderate pain, 30% severe pain, and 5 mild pain. 37.55% of participants had an infection at Grade 0, while 33.3%) were in grades 1 and 2. After one day, 43.3% needed assistance with daily activities, and 46.67% had trouble performing tasks. Sitting baths and infrared therapy effectively reduced pain and discomfort in postpartum mothers. Sitting baths were found to be more effective in pain relief and wound healing. Conclusion:The study found a significant relationship between demographic variables and planned interventions like sitz bath and infrared light instillation for wound healing. Clinical variables, healing process, and infection grades were also related to interventions and duration of episiotomy skin infection. The research hypothesis was accepted, indicating the effectiveness of these treatments.